Analisis Kontrastif Afiksasi Verba Bahasa Jawa Dialek Banten (Bebasan) dan Bahasa Indonesia serta Implikasinya Terhadap Pembelajaran di SMP - Aulia, Winda; Asep Muhyidin; Ade Anggraini Kartika Devi (Metakognisi, 2025)
This research is motivated by the issue of the influence of the mother tongue or first language, which creates obstacles for language learners in acquiring the second language, understanding it, forming sentence structures, and facing difficulties in pronunciation. In relation to this, the research conducts a contrastive analysis of verb affixation. The languages studied are the Banten Dialect of Javanese (Bebasan) and Indonesian, with data taken from the speech of the community in Kampung Baru, Kosambironyok Village, Anyar District, Banten. The method used in this study is qualitative descriptive with an intralingual comparison analysis method, employing the basic techniques of Similar Comparison (HBS) and Different Comparison (HBB). Data collection techniques in this study include structured interviews, recording techniques, and note-taking techniques. The findings of this study indicate both similarities and differences in verb affixation between the Banten Dialect of Javanese and Indonesian. The similarities include: 1) the similarity of the alignment of affixes in the Banten Dialect of Javanese and Indonesian; 2) the similarity in the form of affixed verbs, including phonological structure of affixes, lexical forms, and the similarity in fully affixed verb forms in both languages; 3) the similarity in word types in the lexemes forming affixed verbs, including verbs, nouns, and adjectives. The differences include: 1) differences in the phonological structure of affixes; 2) differences in the process of forming affixed verbs with the prefix N- and the combination of affixes with the suffix –aken in the Banten Dialect of Javanese, which are not found in Indonesian. The research results showing the differences and similarities in verb affixation can be used as a suggestion for creating a module for teaching Indonesian in ninth-grade junior high school classes. Keywords: contrastive analysis, speech, affixed verb